The Influence of Snakes and Ladders Game Media, Concrete Media and Initial Skills on Mathematics Learning Outcomes - Siti Sangiddah; Ibut Priono Leksono; Retno Danu Rusmawati (UNDIKMA, 2023)
This study aims to determine the use of snakes and ladders game media, concrete media, and initial skills can improve student learning outcomes. This methode f research is experimental research using a positivism-quantitative approach. The subjects of this study were students at SDN Jumputrejo class VB and class VC and SDN Sukodono I in-class VA and VB, amount 80 students. The data collection technique in this study is a questionnaire and the test technique is a questionnaire. Technical data analysis using SPSS. Based on the results of the study it was concluded that there were differences in the average score of mathematics learning outcomes in classes taught using snakes and ladders learning media and concrete media with the initial skills of students in the experimental group, students who were taught with the snakes and ladders game media obtained higher learning outcomes compared to the control group or the group taught with concrete media and there was an interaction effect between the snakes and ladders game media and concrete media and initial abilities in mathematics learning outcomes.